Feasibility of Non-Fasting Before Coronary Angiography and Angioplasty: A Safety and Outcomes Study - Mahaseth, Aditya; Lamichhane, Aayush; Sharma, Anubhav; Dhungana, Sahadev; Sayami, Arun (Journal of Nobel Medical College, 2025)
Background: Traditionally, preprocedural fasting before coronary angiography and angioplasty is recommended to reduce the risk of aspiration during sedation. However, prolonged fasting causes patient inconvenience, hypoglycemia, and procedural delays. Recent evidence suggests that fasting may not always be necessary. Materials and Methods: This was a prospective, observational study conducted at Kathmandu Medical College and Teaching Hospital. Patients were selected using simple random sampling and allocated into fasting and non-fasting groups. 400 adult patients scheduled for elective coronary angiography or PCI were randomly assigned to a fasting group (nil per os ≥6 hours, n = 200) or a non-fasting group (light meal ≥4 hours prior, clear liquids allowed up to 2 hours prior, n = 200). The primary outcome was aspiration-related complications (cough, desaturation, or radiographic changes). Secondary outcomes included procedural delay, hypoglycemia, nausea, and patient satisfaction (Likert scale). Logistic regression adjusted for age, sex, diabetes, hypertension, and procedure type. Results: Aspiration-related events were rare and occurred equally in both groups (0.5% each; OR 1.0, 95% CI 0.06–16.1; p = 1.0). Non-fasting patients had significantly fewer procedural delays (1.5% vs. 7.5%; OR 0.19, 95% CI 0.05–0.64; p = 0.002) and hypoglycemia events (0.5% vs. 5.0%; OR 0.09, 95% CI 0.01–0.73; p = 0.005). Patient satisfaction was higher in the non-fasting group (4.7 ± 0.5 vs. 3.5 ± 0.8; mean difference 1.2, 95% CI 0.9–1.5; p < 0.001). Conclusion: The study found no significant difference in the primary outcome of aspiration-related complications between the fasting and non-fasting groups.